Physical rehabilitation and Rehabilitation of Children with Cerebral Palsy, Organization of Psychological Services Parent Support. (Texas Journal of Medical Science, 2023)
Organization and improvement of medical-rehabilitation, psychological and pedagogical assistance to children with cerebral palsy in the information consulting service of the Fergana branch of the RCSAD. Organization of a service of psychological and methodological support to parents